2019
DOI: 10.3329/bjb.v48i2.47549
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antimicrobial and cytotoxic effects of four Turkish species of Eryngium L.

Abstract: The antimicrobial and cytotoxic effects of various endemic and non-endemic Eryngium species from Turkey were investigated. Nine endemic and two non-endemic Eryngium species were analyzed using a microdilution assay for their antibacterial and antifungal activities. Cytotoxic activities of E. pseudothoriifolium, E. thorifolium, E. davisii, and E. falcatum, on prostate carcinoma and endometrial cancer cells were analyzed by cytotoxic activity assay. It was observed that 16 out of 22 extracts (aerial or root part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…[ 46 ]. Finally, it has been demonstrated that E. falcatum exhibits modest antibacterial activity against S. epidermidis and of S. aureus [ 77 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 46 ]. Finally, it has been demonstrated that E. falcatum exhibits modest antibacterial activity against S. epidermidis and of S. aureus [ 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…In another study investigating the essential oil of C. flammula, the major compound identified was furan protoanemonin (75) [138]. According to the study by Boroomand et al (2018), the main constituents of R. arvensis essential oil include polycyclic sesquiterpene guaiol (76), caryophyllene (59), terpenoid spathulenol (77), and the bicyclic monoterpene ketone camphor (47) [139]. The literature review indicates that there is considerable variation in the essential oil composition among different species of Eryngium as well as within the same species.…”
Section: Terpenoidsmentioning
confidence: 99%
See 1 more Smart Citation